2014
DOI: 10.1007/s13277-014-2235-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Aberrant promoter methylation of the CHD1 gene may contribute to the pathogenesis of breast cancer: a meta-analysis

Abstract: Cadherin-1 (CHD1), as an invasion suppressor gene, could suppress tumor cell invasion and metastasis in various tumors, but reduced CHD1 levels, resulting from epigenetic silencing, are common in poorly differentiated, advanced stage carcinomas. This meta-analysis was performed to evaluate the relationships between promoter methylation of CHD1 and breast cancer. Relevant studies were retrieved from the Web of Science (1945 ~ 2013), the Cochrane Library (Issue 12, 2013), PubMed (1966 ~ 2013), EMBASE (1980 ~ 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, CHD1 has been researched to have different effects on different cancers. For example, CHD1 is a tumour suppressor in prostate cancer and oesophageal cancer while it seems to exert as an oncogene in breast cancer . Interestingly, Rodrigues, LU, et al uncover that loss of CHD1 promotes aggressive prostate cancer ; however, Zhao, D., et al revealed that knockdown of CHD1 inhibits tumour growth of PTEN‐null prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CHD1 has been researched to have different effects on different cancers. For example, CHD1 is a tumour suppressor in prostate cancer and oesophageal cancer while it seems to exert as an oncogene in breast cancer . Interestingly, Rodrigues, LU, et al uncover that loss of CHD1 promotes aggressive prostate cancer ; however, Zhao, D., et al revealed that knockdown of CHD1 inhibits tumour growth of PTEN‐null prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CHD1 is a tumour suppressor in prostate cancer and oesophageal cancer 33,34 while it seems to exert as an oncogene in breast cancer. 20,35 Interestingly, Rodrigues, LU, et al uncover that loss of CHD1 promotes aggressive prostate cancer 36 ; however, Zhao, D., et al revealed that knockdown of CHD1 inhibits tumour growth of PTEN-null prostate cancer. 37 In our study, CHD1 was demonstrated to be an oncogene in glioma and positively regulated by MATN1-AS1 but negatively regulated by miR-200b/c/429 in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all exposed individuals develop lung and breast cancers, suggesting that genetic factors play a role in these conditions. A previous meta-analysis demonstrated that the cadherin-1 gene may be involved in the pathogenesis of breast cancer (Gu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%